Serotonin receptor gene (HTR2A) T102C polymorphism modulates individuals’ perspective taking ability and autistic-like traits - Gong, Pingyuan; Liu, Jinting; Blue, Philip R.; Li, She; Zhou, Xiaolin (Frontiers in Human Neuroscience, 2015)
Previous studies have indicated that empathic traits, such as perspective taking, are associated with the levels of serotonin in the brain and with autism spectrum conditions. Inspired by the finding that the serotonin receptor 2A gene (HTR2A) modulates the availability of serotonin, this study investigated to what extent HTR2A modulates individuals’ perspective taking ability and autistic-like traits. To examine the associations of the functional HTR2A polymorphism T102C (rs6313) with individuals’ perspective taking ability and autistic-like traits, we differentiated individuals according to this polymorphism and measured empathic and autistic-like traits with Interpersonal Reactivity Index (IRI) and Autism-Spectrum Quotient (AQ) scale in 523 Chinese people. The results indicated that this polymorphism was significantly associated with the scores on Perspective Taking and Personal Distress subscales of IRI, and Communication subscale of AQ. Individuals with a greater number of the C alleles were less likely to spontaneously adopt the point of view of others, more likely to be anxious when observing the pain endured by others, and more likely to have communication problems. Moreover, the genotype effect on communication problems was mediated by individuals’ perspective taking ability. These findings provide evidence that the HTR2A T102C polymorphism is a predictor of individual differences in empathic and autistic-like traits and highlight the role of the gene in the connection between perspective taking and autistic-like traits.